PEMBELAJARAN KESENIAN HADRAH PADA KOMUNITAS AL-AMIN DI KELURAHAN PAL 5 KOTA PONTIANAK - Satria, Bayu; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Background of this research is about Hadrah Art Learning Process that held in Al-Amin Community. The problem in this research is about How to make a learning method, and hadrah learning process in Al-Amin community in Kelurahan Pal 5, Pontianak City. The method in this research is descriptive method. Forms of this study is qualitative. The approach in this study is a musicological approach. The data in this study were interviews, observation, documentation and results of diaries about the process of learning the arts hadrah. The data used in the study were the resource persons who understand and knew the way to learning the art of hadrah. Data collection techniques in this research is observation, interview, and documentation. Data collection tool in this study were researchers as the main instrument. Checking the validity of the data in this study is an extension of the observation and triangulation of sources. Data analysis techniques in this research is the analysis during data collection and analysis after data collection Keywords: Art HadrahÂ of Learning, Al-Amin Community Â